NATURALISASI FILSAFAT ISLAM DALAM PEMIKIRAN AL-GHAZALI - Ridhatullah Assyabani (UIN Antasari Banjarmasin, 2020)
The thought of al-Ghazali as outlined in Tahafut al-Falasifah has been a controversy for centuries and even today it has become a debate mainly related to the view of al-Ghazali who deconstructed the building of philosophy in Islam resulting in old wounds. In the end, various negative stigmas directed at al-Ghazali. However, whether the work of al-Ghazali, as many have suspected, has resulted in haunting in philosophy or just the opposite? By re-reading al-Ghazali as a traditionalist scholar and reviewing the general opinion which says that Tahafut al-Falasifah is a representation of the conflict between philosophy and dogma; or between orthodoxy and heterodoxy, this paper will show that al-Ghazali has an important role in naturalizing science and philosophy in the frame of Islamic theology.Pemikiran al-Ghazali yang tertuang pada Tahafut al-Falasifah menjadi kontroversi selama berabad-abad, bahkan hingga saat ini menjadi perdebatan terutama terkait dengan pandangan al-Ghazali yang mendekonstruksi bangunan filsafat dalam Islam mengakibatkan luka lama. Pada akhirnya berbagai macam stigma negatif yang ditujukan kepada al-Ghazali. Namun, apakah karya al-Ghazali tersebut seperti banyak yang diduga, telah mengakibatkan kehancuran dalam fisafat atau justru sebaliknya? Dengan melakukan pembacaan ulang terhadap al-Ghazali sebagai ulama tradisionalis dan meninjau pendapat umum yang mengatakan bahwa Tahafut al-Falasifah merupakan representasi konflik antara filsafat dan dogma; atau antara ortodoksi dan heterodoksi, tulisan ini akan memperlihatkan bahwa al-Ghazali memiliki peran penting dalam melakukan naturalisasi filsafat dalam bingkai teologi Islam.